Kebutuhan Air Irigasi pada D.I Krueng Pasee Aceh Utara - Hafli, Teuku Mudi; Desmi, Adzuha; Fadhliani, F; Khairullah, K; Ramadhan, Syahri; Putri, Batari (Malikussaleh Journal of Mechanical Science and Technology, 2023)
Water demand is the amount of water volume that must be met for irrigation, in the Krueng Pasee irrigation area of North Aceh has an irrigation network area of 5579 Ha. The purpose ofthis research is to obtain the maximum and minimum irrigation water demand discharge in the study area. This research can be an additional source of knowledge for writers in particular and for readers in general. As well as the results of this study can be known the value of rice planting water needs. The data used in the research is rainfall data sourced from BMKG (Meteorology, Climatology, and Geophysics Agency) Malikussaleh, used to calculate effective rainfall and climate data sourced from BMKGMalikussaleh in the form of temperature data, solar irradiation data, wind speed data and humidity or temperature data used to calculate evapotranspiration (ETo). ETo is a combination of evaporation and transpiration which is defined as the event of water loss from plant tissue and the surface of the soil usedas a place to grow plants. In analyzing ETo using the Penman Modification Methodology. The Penman method by adjusting the wind function according to local conditions produces the best approach to the evapotranspiration rate of the lysimeter results. The consumptive use of plants (ETc) during the land preparation period uses the results of the calculation of water requirements for land preparation (IR). Crop consumptive use (ETc) after land preparation is a calculation between evapotranspiration and cropcoefficient. The calculated irrigation water requirement (NFR) results in water requirement in the form of mm/day. Irrigation water requirements are converted to l/dt/ha with a conversion rate of 1/8.64. The smallest water demand calculation discharge was obtained in November-1 at Q = 4.32 m3/det and thelargest water demand in February -1 at Q = 13.40 m3/det. At the research location, rice planting begins in January-I, with a rice-soybean planting pattern. From the calculation of water demand, Krueng Pasee Irrigation Area has the smallest water demand in November-1 and the largest water demand in February-1.